Modification of a direct enzyme-linked immunosorbent assay for the detection of immunoglobulin G and M antibodies to pneumococcal capsular polysaccharide. - Messina, J P (1985)
In contrast to the usual indirect enzyme-linked immunosorbent assay (ELISA) method for detection of antibody responses, a modified direct ELISA technique was used to measure immunoglobulin G (IgG) and IgM responses to pneumococcal capsular types 1, 3, 9N, and 23F in humans. Individual capsular polysaccharides were covalently bound to poly-L-lysine before adsorption to the solid phase. The coupling reaction was enhanced by maintenance of a constant pH of 8.2 after the addition of all reactants. The evaluation of four diluents (phosphate-buffered saline [PBS]-Tween; PBS-Tween plus 10% fetal calf serum; PBS-Tween plus 10% bovine serum albumin; and PBS-Tween plus 20% normal goat serum) showed that the sensitivity and specificity of the assay was increased with normal goat serum (10-fold). Serum samples from 10 subjects immunized with polyvalent pneumococcal vaccine were tested by direct ELISA and by radioimmunoassay. At 4 weeks postimmunization, the ELISA method showed that IgG was the predominant antibody and that IgM responses were lower or had diminished. Isotype shifts during this period would have been undetected by the radioimmunoassay method. The changes in antibody response measured by ELISA were comparable to the radioimmunoassay results. The direct ELISA method for the detection of antipneumococcal capsular antibody has been found to be a sensitive and reproducible assay for the detection of IgG and IgM antibodies.